Estudo da sinterização do aço inox 316L reforçado com 3% Carbeto de Tântalo - TaC - Oliveira, Leiliane Alves de (2008)
The present work shows a contribution to the studies of development and solid sinterization of a metallic matrix composite MMC that has as starter materials 316L stainless steel atomized with water, and two different Tantalum Carbide TaC powders, with averages crystallite sizes of 13.78 nm and 40.66 nm. Aiming the metallic matrix s density and hardness increase was added different nanometric sizes of TaC by dispersion. The 316L stainless steel is an alloy largely used because it s high resistance to corrosion property. Although, its application is limited by the low wear resistance, consequence of its low hardness. Besides this, it shows low sinterability and it cannot be hardened by thermal treatments traditional methods because of the austenitic structure, face centered cubic, stabilized mainly in nickel presence. Steel samples added with TaC 3% wt (each sample with different type of carbide), following a mechanical milling route using conventional mill for 24 hours. Each one of the resulted samples, as well as the pure steel sample, were compacted at 700 MPa, room temperature, without any addictive, uniaxial tension, using a 5 mm diameter cylindrical mold, and quantity calculated to obtain compacted final average height of 5 mm. Subsequently, were sintered in vacuum atmosphere, temperature of 1290ºC, heating rate of 20ºC/min, using different soaking times of 30 and 60 min and cooled at room temperature. The sintered samples were submitted to density and micro-hardness analysis. The TaC reforced samples showed higher density values and an expressive hardness increase. The complementary analysis in optical microscope, scanning electronic microscope and X ray diffractometer, showed that the TaC, processed form, contributed with the hardness increase, by densification, itself hardness and grains growth control at the metallic matrix, segregating itself to the grain boarders